Penerapan Model Penelitian Tindakan Kelas untuk Meningkatkan Kualitas Pendidikan Karakter - Siregar, Isropil; Nurhasan, Nurhasan; Ilhamsyah, Rizal (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
This study aims to analyze the application of the classroom action research (CAR) model in an effort to improve the quality of character education at the Ihsanul Qur'an Islamic Boarding School. Character education is an important aspect in shaping the morals and behavior of students, which functions to prepare a generation that has high moral and spiritual values. Through CAR, educators can identify problems, plan actions, implement interventions, and reflect on the results obtained. This study was conducted in two cycles, involving 30 students as research subjects. Data collection methods were carried out through observation, interviews, and questionnaires. The results of the study showed a significant increase in positive attitudes and behavior of students, which was reflected in changes in active participation in religious and social activities. In addition, teacher and student reflections during the research process also indicated a higher awareness of the importance of character education. In conclusion, the application of the CAR model at the Ihsanul Qur'an Islamic Boarding School is effective in improving the quality of character education of students, and can be a model for other Islamic boarding schools in developing character education.